O negócio da música sertaneja no Brasil: tocando as emoções, as relações, o corpo e a alma - Rhormens, Diego Paulo (2018)
Country music is taking the centrality of many events and the media, being the most played and listened music genre in Brazil. This work aims at understanding the social and cultural benefits of country music and its market dynamic in Brazil, from the point of view of the different professionals involved in its production and communication. The research focused on perceiving what are the functions of the different professionals involved in the production and communication of country music, comprehending the factors that led to the great public support to its culture, assessing what are the benefits proportioned to individuals by its songs from the social and cultural standpoint, and understanding the importance of television, radio and internet in its culture. This work is justified in the view of creative economy importance in the Brazilian cultural scene and by the need of better discerning this business to the benefit of country music industry professionals. This work is also upheld by the fact that country music is a cultural asset, which relates to individuals values, traditions, relationships, memories and affections, and therefore cannot be treated merely as a commercial issue, but must be respected in its cultural and social context. The research methodology consisted on reviewing the theme´s bibliography and carrying out eight interviews with different music scene agents that were further analyzed. Through the interviews, it was possible to establish that, when country songs are played in events, they favor many kinds of individual connections, such as new friendships, love relationships, among others. Song lyrics are full of stories with feelings and emotions, and may enable individuals to identify themselves with what is being sung by artists, specially regarding to love relationships and its developments. Traditional country music is a Brazilian historical and cultural heritage that portrays the life in the countryside. There are many professionals working directly with the music industry in different functions and putting together their skills to take culture to the audience, given that music is art, but is also inserted in a market logic